2020
DOI: 10.3390/ijerph17031025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biological Toxicity and Ecological Safety for Urban Black-Odor River Remediation

Abstract: The judgment and assessment of remediation effect on urban black-odor river still depend on the physical-chemical parameters and lack in ecological safety effects. A set of combined biological toxicity tests were applied to evaluate the ecological effects of one urban black-odor river before and after the remediation. The special growth rate of Chlorella vulgaris and mortality rate of Daphnia magna were used to assess acute toxicity. The Salmonella Typhimurium/Reverse Mutation Assay was applied to test the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The D. magna is commonly employed as a model organism given that it is a common member of aquatic invertebrate communities. Furthermore, D. magna is often considered a bioindicator species for studying environmental contamination because it has a short generation time, can be easily cultivated, and is sensitive to a wide range of contaminants [ 35 , 36 , 37 ]. Accordingly, determining the physiological and biochemical responses of D. magna to the dewatered DWTR could provide essential information about the safety of recycling DWTR in environmental remediation.…”
Section: Discussionmentioning
confidence: 99%
“…The D. magna is commonly employed as a model organism given that it is a common member of aquatic invertebrate communities. Furthermore, D. magna is often considered a bioindicator species for studying environmental contamination because it has a short generation time, can be easily cultivated, and is sensitive to a wide range of contaminants [ 35 , 36 , 37 ]. Accordingly, determining the physiological and biochemical responses of D. magna to the dewatered DWTR could provide essential information about the safety of recycling DWTR in environmental remediation.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic organisms at different levels of the food chain respond differently to toxicity. Xu et al (2020) studied the biotoxicity of porewater in black odiferous water and found that the toxicity levels of sediment porewater to D. magna and Chlorella vulgaris were different at the same site. Moreover, various factors in the actual environment can influence the toxic effect, and multiple pollutants in the environment may also have different combined toxicities.…”
Section: Ecological Risk Assessment Of Three Pas In the Soil Environmentmentioning
confidence: 99%